The Importance of Communicating your COVID-19 Health and Safety Measures: A Marketing Experiment on Hotel Bookings using Eye-tracking - Otilia-Elena PLATON; David-Florin CIOCODEICĂ; Raluca-Giorgiana (POPA) CHIVU (Communications of International Proceedings, 2021)
The COVID-19 pandemic altered customers’ evaluations of tourism and hospitality products and services, especially in terms of hygienic requirements. This pandemic created a new and fundamental dimension in the process of evaluating tourism products, namely the health security. During these challenging times, every business involved in the tourism and hospitality industry needs to understand how to ease customers’ concerns and how to manage customers’ expectations regarding health and cleanliness in order to inspire confidence and help turn demand into bookings. To better comprehend all these changes, the present article focuses on the importance of communicating COVID-19 health and safety measures in the tourism industry in order to gain consumers’ trust and to reduce their anxiety and insecurities. The exploratory quantitative research, developed for this article, aimed to identify the influence of safety measures taken by accommodation units on customers’ decision to book a certain hotel during COVID-19 pandemic. The research was based on an online experiment that used an online eye-tracking software and an online questionnaire as data-gathering tools. Insights obtained from this research can help hospitality properties to better understand the importance of communicating safety measures during this pandemic and adjusting to possibly longer-lasting shifts in consumer preferences. Such an experiment can offer knowledge for practitioners to better serve customers in their business operation.
Keywords: Tourism Industry; COVID-19; Safety Measures; Hotel Evaluation; Marketing Experiment